Nocturnal Hypoglycemia in Patients With Diabetes Discharged From ICUs: A Prospective Two-Center Cohort Study*. Issue 4 (April 2021) - Ali Abdelhamid, Yasmine; Bernjak, Alan; Phillips, Liza K.; Summers, Matthew J.; Weinel, Luke M.; Lange, Kylie; Chow, Elaine; Kar, Palash; Horowitz, Michael; Heller, Simon; Deane, Adam M.
Abstract : OBJECTIVES: There is very limited information about glycemic control after discharge from the ICU. The aims of this study were to evaluate the prevalence of hypoglycemia in ICU survivors with type-2 diabetes and determine whether hypoglycemia is associated with cardiac arrhythmias. DESIGN: Prospective, observational, two-center study. Participants underwent up to 5 days of simultaneous blinded continuous interstitial glucose monitoring and ambulatory 12-lead electrocardiogram monitoring immediately after ICU discharge during ward-based care. Frequency of arrhythmias, heart rate variability, and cardiac repolarization markers were compared between hypoglycemia (interstitial glucose ⩽ 3.5 mmol/L) and euglycemia (5–10 mmol/L) matched for time of day. SETTING: Mixed medical-surgical ICUs in two geographically distinct university-affiliated hospitals. PATIENTS: Patients with type-2 diabetes who were discharged from ICU after greater than or equal to 24 hours with greater than or equal to one organ failure and were prescribed subcutaneous insulin were eligible. MEASUREMENTS AND MAIN RESULTS: Thirty-one participants (mean ± SD, age 65 ± 13 yr, glycated hemoglobin 64 ± 22 mmol/mol) were monitored for 101 ± 32 hours post-ICU (total 3, 117 hr). Hypoglycemia occurred in 12 participants (39%; 95% CI, 22–56%) and was predominantly nocturnal (40/51 hr) and asymptomatic (25/29 episodes). Participants experiencing hypoglycemia had 2.4 ± 0.7 discrete episodes lasting 45 minutes (interquartile range, 25–140 min). Glucose nadir was less than or equal to 2.2 mmol/L in 34% of episodes. The longest episode of nocturnal hypoglycemia was 585 minutes with glucose nadir less than 2.2 mmol/L. Simultaneous electrocardiogram and continuous interstitial glucose monitoring recordings were obtained during 44 hours of hypoglycemia and 991 hours of euglycemia. Hypoglycemia was associated with greater risk of bradycardia but did not affect atrial or ventricular ectopics, heart rate variability, or cardiac repolarization. CONCLUSIONS: In ICU survivors with insulin-treated type-2 diabetes, hypoglycemia occurs frequently and is predominantly nocturnal, asymptomatic, and prolonged. Abstract : Supplemental Digital Content is available in the text.